Analisis Potensi Bahaya Dengan Menggunakan Metode Job Safety Analysis Di Bagian Mold Maintenance PT XYZ Plant Cikarang - Andriani, Andriani; Suwarno, Agus (JURNAL TEKNIK INDUSTRI, 2022)
PT. XYZ is one of the large companies operating in the automotive sector as a manufacturer of two -wheeled and four -wheeled vehicles. In the production process, there are various types of plants, one of which is the die casting plant which focuses on the manufacture of cylinder heads. Inside the die casting, there is a part responsible for caring for and maintaining the mold or cylinder head mold, which is the mold maintenance part. Every workplace will always have the possibility of occupational accidents and illnesses. To control the risk of occupational accidents and diseases, it is necessary to identify the causes of hazards in the workplace and assess the level of risk so that adequate control and prevention of occupational accidents can be carried out. The incidence of accidents and injuries in the workplace can be reduced by using Occupational Safety Analysis. At one stage of the dies maintenance process, the upper dies cleaning process is carried out by the mold maintenance section. In the process, there is the potential for work accidents to be cut, pinched, exposed to sharp fragments and crushed by molds that stand without support. The purpose of this study was to analyze the potential hazards in the process and action of upper dies cleaning. The research methods used in this research are descriptive and observational qualitative research. By conducting interviews with operators who run the process, in addition to conducting interviews, researchers also make observations about how operators work in the process. The method of analytical study is to see or observe and carry out the upper die cleaning process before any improvement, seen the potential for work accidents is very high because workers sit and carry out the cleaning process behind the upper die which is standing without safety. The potential hazards that may occur at the upper dies cleaning process stage are upper dies weighing up to 500 kg. The advice given is to develop by creating tools. The purpose of this tool is to support the back of the upper die so that it does not fall during the cleaning process and reduce as well as avoid work accidents.